2013
DOI: 10.1159/000355956
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Primary Mesh Augmentation as Prophylactic Measure to Prevent Incisional Hernia

Abstract: Background: Incisional hernia (IH) remains one of the most frequent postoperative complications after abdominal surgery. As a consequence, primary mesh augmentation (PMA), a technique to strengthen the abdominal wall, has been gaining popularity. This meta-analysis was conducted to evaluate the prophylactic effect of PMA on the incidence of IH compared to primary suture (PS). Methods: A meta-analysis was conducted according to the PRISMA guidelines. Randomized controlled trials (RCTs) comparing PMA and PS for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 81 publications
(89 reference statements)
6
45
1
2
Order By: Relevance
“…3. Timmermans et al [104] published a good metaanalysis on five RCT's using polypropylene mesh, including a RCT published in 2013 by Abo-Ryia et al [105].…”
Section: Prophylactic Mesh Augmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Timmermans et al [104] published a good metaanalysis on five RCT's using polypropylene mesh, including a RCT published in 2013 by Abo-Ryia et al [105].…”
Section: Prophylactic Mesh Augmentationmentioning
confidence: 99%
“…Using Review Manager 5.2 software a new meta-analysis was performed. The data for this meta-analysis were extracted from the Timmermans et al metaanalysis and the additional RCT [104,106]. A meta-analysis on the outcomes of incisional hernia, seroma and SSI was performed.…”
Section: Prophylactic Mesh Augmentationmentioning
confidence: 99%
“…There is abundant evidence of treatment modalities and outcome of incisional hernia repair once a hernia has been developed [36][37][38][39][40] but data regarding protection against incisional hernia by the prophylactic prosthetic reinforcement of midline abdominal incisions is scarce and particularly focused on high-risk patients and permanent synthetic materials placed similarly as an incisional hernia is repaired (onlay, sublay, etc.) [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Also, a new device (made of polypropylene and expanded polytetrafluoroethylene in the shape of an upside-down T) has been specifically designed to be placed between the two edges of the incision site to buttress the linea alba [19]. Recently, systematic reviews and meta-analyses have shown that these preventive measures may contribute to minimizing the rates of incisional hernia in high-risk patients [20][21][22]. Long-term potential complications (such as hernia recurrence, enterocutaneous fistula, bowel obstruction, infection, or chronic pain triggered in the host) related to these everlasting materials have been reported [12,14,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to concerns for residual confounding due to unmeasured variables, these database analyses are limited by the lack hernia specific data such as mesh type and lack of reporting of outcomes beyond 30 d. Further evidence regarding the safety of mesh in contaminated ventral hernia repairs has been extrapolated from randomized controlled trials of prophylactic mesh placement in wound class II cases. These trials have demonstrated that mesh placement can reduce the risk of hernia formation without increasing the risk of SSI [10]. Caution should be used in generalizing these results to ventral hernia repairs, particularly complex ventral hernia repairs.…”
Section: Introductionmentioning
confidence: 99%